The Anxious Generation: Why Student Wellbeing is the New Core Curriculum - Amiri, Sayed Mahbub Hasan (Universitas Negeri Surabaya, 2026)
A profound shift is occurring in educational paradigms, moving beyond a narrow focus on academic achievement to embrace student wellbeing as a fundamental component of school success. Dubbed